Finite Difference Method for the Reverse Parabolic Problem - Charyyar Ashyralyyev; Ayfer Dural; Yasar Sozen (Abstract and Applied Analysis)
A finite difference method for the approximate solution of the reverse multidimensional parabolic differential equation with a multipoint boundary condition and Dirichlet condition is applied. Stability, almost coercive stability, and coercive stability estimates for the solution of the first and second orders of accuracy difference schemes are obtained. The theoretical statements are supported by the numerical example.